Measurements of pressure and area dependent tangential contact stiffness between rough surfaces using digital image correlation - Kartal, M; Mulvihill, D; Nowell, D; Hills, D (2011)
The present paper describes an experimental technique to accurately measure the tangential contact stiffness between two rough contacting surfaces manufactured from the titanium alloy Ti6Al4V. The digital image correlation method is employed to measure the local displacement field. The effect of normal contact pressure, nominal contact area and fretting wear on tangential contact stiffness is investigated. The experiments indicate that the tangential contact stiffness is approximately proportional to the nominal contact area and the normal pressure raised to the power of 0.64. Multiple experiments with the same parameters show good repeatability given the number of variables involved. © 2011 Elsevier Ltd. All rights reserved.